Accompaniment On Parents In Increasing Children’s Learning Interest In The Covid-19 Pandemic - M Dahlan; Rizcka Fatiya (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
This guidance aims to: (1) encourage student guardians to increase their children's interest in learning during the Covid-19 pandemic at SDN Dukuh 01; (2) identify ways to increase student interest in learning during the Covid-19 pandemic at SDN Dukuh 01; and (3) raise parents' awareness of the importance of their children's education. The guardianship training was done via a WhatApp group that included parents and guardians of grade 2 and 3 pupils at SDN Dukuh 01, totaling 48 guardians. Parents frequently accompany their children to study at home, according to the findings of processing the questionnaire data given after the parents have finished coaching 80 percent of the pupils. And 70% of parents frequently motivate their children at home while they are learning. 70 percent of parents and guardians of students establish a comfortable environment for their children to study at home, and 60 percent of parents vary and innovate their children's everyday activities at home to increase their children's interest in learning.